The Role of Diaspora in Realizing Indonesia’s Economic Resilience - Imam Hamdani; Maria Puspitasari (Transpublika Publisher, 2025)
The Indonesian diaspora has a strategic role in strengthening national economic resilience through various contributions, such as remittances, investment, knowledge transfer, and economic and cultural diplomacy. This study aims to analyze the role of the diaspora in realizing national economic resilience and identifying the obstacles faced. With a qualitative descriptive approach with literature study. This study discovered four important things related to the role of the diaspora and the obstacles faced, namely first, remittances contribute to household financial stability, economic growth, poverty reduction, and strengthening micro, small, and medium enterprises (MSMEs). Second, remittances sent by the diaspora have proven to be one of the main sources of foreign exchange for Indonesia, which supports household consumption, education, and investment in the productive sector. Third, optimizing the role of the diaspora is still hampered by regulatory constraints, complex bureaucracy, and the lack of policies that support diaspora involvement in national development. Fourth, a more inclusive and systematic policy strategy is needed to integrate the diaspora into national economic policies, so that their potential can be utilized optimally to increase Indonesia's competitiveness and economic resilience. This study recommends that diaspora-related policies be integrated with national economic policies to increase Indonesia's competitiveness and economic resilience. This study contributes academically by integrating diaspora engagement with economic resilience theory which is an underexplored area in Indonesia. Likewise, it bridges policy discourse with diaspora studies, offering novel perspectives that enrich literature while recommending alignment of diaspora initiatives with national economic objectives to enhance Indonesia's global competitiveness.